Application of surface response methodology to optimize hydrolysis of wheat gluten and characterization of selected hydrolysate fractions - Drago, Silvina Rosa (2008)
BACKGROUND: The aim of this work was to optimize the hydrolysis experimental conditions to obtain wheat gluten hydrolysates and to characterize fractions from hydrolysates with different hydrolysis degrees in order to develop protein functional ingredients. Surface response methodology was used to analyze the effect of reaction factors on the degree of hydrolysis to assess the conditions for maximum fungal protease enzyme activity. Hydrolysates having three different trichloroacetic acid indices (TCAI) were prepared. Soluble fractions at pH 4, 6.5 and 9 from these hydrolysates were characterized by electrophoresis, reverse-phase high-performance liquid chromatography, free amino group content and peptide chain length. RESULTS: Temperature and pH ranges for highest enzyme activity at 2.5 h were 54–58 ◦C and 4.2–4.4, respectively. Hydrolysate fraction composition differs according to the hydrolysis degree and extracting pH, the difference being more pronounced at low TCAI. Hydrolysate having 32% TCAI is composed of peptides whose size is lower than 18.5 kDa, with an average peptide chain length of 14 amino acid residues. CONCLUSION: The combination of hydrolysis degree and pH of extraction allows fractions of different peptide composition to be obtained, which could be taken into account when trying to find a defined composition related to determined functional characteristics.